2017
DOI: 10.3855/jidc.9146
|View full text |Cite
|
Sign up to set email alerts
|

Ochrobactrum anthropi: An emerging pathogen causing meningitis with sepsis in a neurotrauma patient

Abstract: Ochrobactrum anthropi is an unusual emerging pathogen especially in the hospital environment. Most of the reported cases are nosocomially acquired infections in patients with various indwelling and invasive medical devices, such as central venous catheters and drainage tubes. We report a case of nosocomially transmitted invasive catheter related septicaemia with meningitis due to O. anthropi, in an elderly immunocompetent male with a head trauma admitted to a level -1 trauma centre. This report describes clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 9 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…(Mudshingkar et al, 2013;Arora et al, 2008). Recently, Rastogi et al, reported a case describing disseminated infection causing meningitis and blood stream infection due to O. anthropi in an immunocompetent trauma patient (Rastogi et al, 2017). Opportunistic infections caused by O. anthropi have also been reported from abroad by various workers (Kettaneh et al, 2003;Khan et al, 2014;Cieslak et al, 1992;Vaidya et al, 2006;Duran et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Mudshingkar et al, 2013;Arora et al, 2008). Recently, Rastogi et al, reported a case describing disseminated infection causing meningitis and blood stream infection due to O. anthropi in an immunocompetent trauma patient (Rastogi et al, 2017). Opportunistic infections caused by O. anthropi have also been reported from abroad by various workers (Kettaneh et al, 2003;Khan et al, 2014;Cieslak et al, 1992;Vaidya et al, 2006;Duran et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Identification and drug susceptibility of the isolate were performed by VITEK® 2 system (Biomerieux, France) using VITEK 2 GN CARD REF 21341and VITEK® 2 AST-N281 REF414532 card respectively. As the susceptibility to O. anthropi is not documented in CLSI, the antibiogram was reported as per Pseudomonas species (Rastogi et al, 2017). The isolate was susceptible to ciprofloxacin, aminoglycosides and carbapenems but was resistant to penicillin, cephalosporins and colistin (MIC ≥16µg/ml).…”
Section: Introductionmentioning
confidence: 99%
“…They are oxidase-positive, saccharolytic, and motile with peritrichous flagella [ 10 ]. O. anthropi is ubiquitous and widely distributed in soil, plants, and water sources like normal saline, antiseptics, dialysis fluids, and swimming pools and also has been isolated from the hospital environment and contaminated foreign bodies such as intravascular catheters, graft tissues, and clinical specimens [ 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Catheter-related blood stream infection (CRBSI) due to O. anthropi have been documented by Kern WV et al 17 anthropi blood stream infections in immunocompromised patients. 5,13,[15][16][17][19][20][21] However, in 2017, Rastogi N et al 22 observed catheter-related septicaemia with meningitis due to O. anthropi, in an elderly immunocompetent male with a head trauma. Kettaneh A et al 23 documented a case of septic shock that occurred in an otherwise healthy host after administration of a peripheral venous infusion of a solution contaminated with O. anthropi.…”
Section: Discussionmentioning
confidence: 99%